2017
DOI: 10.1055/s-0037-1602163
|View full text |Cite
|
Sign up to set email alerts
|

Rhytidectomy: Analysis of Videos Available Online

Abstract: The objective of this study was to examine YouTube videos related to rhytidectomy created by both physicians and nonphysicians to determine the content of the videos, the selected topics of discussion, and other important parameters using a cross-sectional analysis study design. A YouTube search result for the keyword “facelift” was performed. Videos pertaining to the rhytidectomy procedure were included in this analysis. Authorship, length of video, primary objective, and total views were recorded. Total 80 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A study reviewed the available surgical videos for rhytidectomy on YouTube and found variability in the videos, many lacking discussions of key aspects of successful surgery and concluded that discretion should be utilized when accessing such videos as a learning tool [10]. A similar study also echoed the finding that the videos available online for rhytidectomy vary greatly and lacking safeguards to report quality or accuracy [44]. A study also assessed the surgical videos of neck dissections on YouTube and noted the quality of the videos widely varied and reported no correlation between the quality and the age and popularity of the video [45].…”
Section: Datamentioning
confidence: 99%
“…A study reviewed the available surgical videos for rhytidectomy on YouTube and found variability in the videos, many lacking discussions of key aspects of successful surgery and concluded that discretion should be utilized when accessing such videos as a learning tool [10]. A similar study also echoed the finding that the videos available online for rhytidectomy vary greatly and lacking safeguards to report quality or accuracy [44]. A study also assessed the surgical videos of neck dissections on YouTube and noted the quality of the videos widely varied and reported no correlation between the quality and the age and popularity of the video [45].…”
Section: Datamentioning
confidence: 99%